ANALISIS STRATEGI PEMASARAN PRODUK BUDIKDAMER DI SMA MUHAMMADIYAH AL’AMIN DISTRIK MALAIMSIMSA KOTA SORONG PROVINSI PAPUA BARAT DAYA - Ellen Loupatty; M. Iksan Badaruddin; Fatimah Hardanti; Christy Radjawane (CV SWA Anugerah, 2024)
Development of the fisheries sector is a Prime Mover that can be used to overcome the economic crisis towards a developed and prosperous Indonesia. However, this potential also has challenges in managing it, especially to obtain optimal and sustainable economic benefits. Indonesia is still working hard to align itself with developed countries that have successfully developed modern, independent and sustainable aquaculture. Freshwater aquaculture fishery products is a form of fisheries resource management that requires good skills, strategies and technology to increase production results. The purpose of this socialization activity is to introduce students or targets to how to get to know the good and successful Budikdamer Method. The method used in this writing is a literature study. Implementation of service activities is carried out using a participatory approach and the analysis used is SWOT Analysis